The fundamentals of science writing - Siraj, Walid Muhamad (Al-Mukhtar Journal of Sciences, 1992)
This paper deals with the fundamentals of science writing in Arabic. It addresses the issues of scientific writing in agriculture, and is applicable to other disciplines, including biology, chemistry, physics and mathematics.